Hantaviral mechanisms driving HLA class I antigen presentation require both RIG‐I and TRIF. Issue 10 (15th July 2013) - Lalwani, Pritesh; Raftery, Martin J.; Kobak, Lidija; Rang, Andreas; Giese, Thomas; Matthaei, Markus; van den Elsen, Peter J.; Wolff, Thorsten; Krüger, Detlev H.; Schönrich, Günther
<x xml:space="preserve">Abstract</x> Hantaviruses are emerging human pathogens. They induce an unusually strong antiviral response of human HLA class I (HLA‐I) restricted CD8+ T cells that may contribute to tissue damage and hantavirus‐associated disease. In this study, we analyzed possible hantaviral mechanisms that enhance the HLA‐I antigen presentation machinery. Upon hantavirus infection of various human and primate cell lines, we observed transactivation of promoters controlling classical HLA molecules. Hantavirus‐induced HLA‐I upregulation required proteasomal activity and was associated with increased TAP expression. Intriguingly, human DCs acquired the capacity to cross‐present antigen upon hantavirus infection. Furthermore, knockdown of TIR domain containing adaptor inducing IFN‐β or retinoic acid inducible gene I abolished hantavirus‐driven HLA‐I induction. In contrast, MyD88‐dependent viral sensors were not involved in HLA‐I induction. Our results show that hantaviruses strongly boost the HLA‐I antigen presentation machinery by mechanisms that are dependent on both retinoic acid inducible gene I and TIR domain containing adaptor inducing IFN‐β.